Modeling Socioeconomic Factors Affecting Age at Marriage among females in Kogi State, Nigeria - Adarabioyo, M. I.; Awe, O. O.; Lawal, F. K. (2014)
This paper is aimed at determining the effect of socioeconomic factors such as cultural background, level of education and religion in relation to age at marriage among women in Kogi State Nigeria. The survey area is made up of diverse ethnic groups with three major languages. The stud) reveals that education is an important factor which increases the age at marriage in the State. The study equally proved that religion and cultural background does not affect age at marriage among women in Kogi State, Nigeria. A Saturated one-way and two-way model was fitted to reveal the behavioral pattern of the distribution.